2013
DOI: 10.1038/ni.2708
|View full text |Cite|
|
Sign up to set email alerts
|

Signaling by Fyn-ADAP via the Carma1–Bcl-10–MAP3K7 signalosome exclusively regulates inflammatory cytokine production in NK cells

Abstract: Inflammation is a critical component of the immune response. However, acute or chronic inflammation can be highly destructive. Uncontrolled inflammation forms the basis for allergy, asthma, and multiple autoimmune disorders. Here, we identify a signaling pathway that is exclusively responsible for inflammatory cytokine production but not for cytotoxicity. Recognition of H60+ or CD137L+ tumor cells by murine NK cells led to efficient cytotoxicity and inflammatory cytokine production. Both of these effector func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 50 publications
(72 reference statements)
7
95
0
Order By: Relevance
“…Triggering of activating NK receptors induces actin polymerization, phosphatidylinositol-3-OH kinase activation and phosphorylation of MEK and ERK, ultimately promoting NK-cell cytotoxicity 14 . We analyzed NK-cell degranulation upon engagement of CD16, NKp30, NKp46 (all of which use CD3ζ and FcεRIγ), or NKG2D (which recruits the DAP10 adaptor), and observed severely impaired degranulation in P1 (Fig.3B), and moderately impaired in P2, likely corresponding to residual amounts of DOCK2 protein in P2’s hematopoietic cells (Fig.S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Triggering of activating NK receptors induces actin polymerization, phosphatidylinositol-3-OH kinase activation and phosphorylation of MEK and ERK, ultimately promoting NK-cell cytotoxicity 14 . We analyzed NK-cell degranulation upon engagement of CD16, NKp30, NKp46 (all of which use CD3ζ and FcεRIγ), or NKG2D (which recruits the DAP10 adaptor), and observed severely impaired degranulation in P1 (Fig.3B), and moderately impaired in P2, likely corresponding to residual amounts of DOCK2 protein in P2’s hematopoietic cells (Fig.S4A).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that cytokine secretion and cytotoxicity can be uncoupled in target-stimulated NK cells 38 . Since the loss of FcεRIγ/Syk module has been associated to an increased IFNγ producing potential, 39 we explored the ability of anti-CD20-experienced NK cells to secrete IFNγ.…”
Section: Resultsmentioning
confidence: 99%
“…Although ADAP is important for optimal interactions between naïve T cells and Ag-laden APCs both in vitro and in vivo (14, 19, 21), there have been conflicting reports on the role of ADAP in killing of target cells by effector CD8 T cells (24, 25) or NK cells (20, 55). One study reported enhanced cytolytic function of ADAP −/− tumor-specific CTLs in vitro and in vivo (23), while another study reported that CD8 CTLs lacking ADAP exhibited normal cytotoxicity in response to an allogenic graft (25).…”
Section: Discussionmentioning
confidence: 99%
“…The downstream effects of TCR-inducible interactions of ADAP with caspase recruitment domain (CARD) membrane-associated guanylate kinase (MAGUK) protein 1 (CARMA-1) and, transforming growth factor-β (TGF-β)-activated protein kinase (TAK-1) promote T cell entry into the cell cycle (9, 1517). The ADAP-CARMA-1-TAK-1 signalosome is also required for cytokine and chemokine production by NK cells after NKG2D or CD137 stimulation (20). …”
Section: Introductionmentioning
confidence: 99%